MENINGKATKAN NILAI TAMBAH PRODUK LOKAL MELALUI PENDAMPINGAN PENGEMASAN DAN PELABELAN KERIPIK PISANG DI DESA SIREMEN, KECAMATAN TANARA KABUPATEN SERANG - Siti Nuriah; Khoeriah Khoeriah; Siti Hodijah; Agung Ramadhan; Wahyu Darma Putra; Watardo Tun Nevahdi; Atoilah Atoilah (Yayasan Education and Social Center, 2023)
This community service program activity aims to identify internal and external factors that influence the banana chip business in Siremen Village, Tanara District, Serang Regency. The main focus is to formulate alternative strategies for developing the banana chip business, given the high demand for this food among the public. In the context of UMKM Pisang Mak Wiyah chips, the main challenges faced lie in management aspects, especially marketing strategy, especially in terms of packaging and labeling management. The initial step taken is to increase understanding of effective packaging and labeling management for businesses and their staff. To achieve this goal, a labeling and packaging training activity was held in Siremen Village, Tanara District, on August 5, 2023. This activity involved the participation of 7 individuals. The method used in carrying out this activity includes lecture and tutorial sessions, which are followed by open discussions. This activity has succeeded in increasing understanding of packaging and labeling management among UMKM Pisang Mak Wiyah chips. Participants not only show high motivation and enthusiasm in participating in this training, but are also actively involved in discussions and interactions. Steps like these have a positive impact on the development of local businesses and have the potential to increase product competitiveness in the market